2005
DOI: 10.1111/j.1365-3083.2005.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sero‐Epidemiological Survey of Gelatin Sensitization in Young Japanese Children During the 1979–1996 Period

Abstract: Recently, an increasing number of adverse reactions in children inoculated with live attenuated virus vaccines containing gelatin have been reported. However, the distribution, magnitude and rate of gelatin sensitization in the Japanese population have not been established. Here, the purpose was to investigate the distribution of children with positive gelatin immunoglobulin G (IgG) and/or IgE in Japan and to ascertain whether the incidence of positive antigelatin antibody cases among the general population, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Egg proteins may also be present in very low amounts in some vaccines that use viruses grown in embryonated eggs, such as the influenza vaccine. These proteins may trigger an allergic response in persons intolerant to this component 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Egg proteins may also be present in very low amounts in some vaccines that use viruses grown in embryonated eggs, such as the influenza vaccine. These proteins may trigger an allergic response in persons intolerant to this component 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the information submitted on the composition of the additives containing beta-carotene the FEEDAP Panel considers it unlikely that such formulations could cause skin/eye irritancy. The FEEDAP Panel notes that a sensitisation risk associated with gelatin is reported in the scientific literature; however, such findings are restricted to its use in vaccines (Pool et al, 2002;Saito et al, 2005). Thus, the FEEDAP Panel considers it unlikely that skin sensitisation may arise in workers exposed to gelatin present in beta-carotene used as a feed additive.…”
Section: Effects On Skin and Eyesmentioning
confidence: 99%
“…Therefore, gelatin has been generally used as a stabilizer in vaccines . However, it was reported that vaccines containing gelatin sometimes cause severe anaphylactic reactions , . Beginning in 1993, anaphylactic reactions were increasingly reported after administration with gelatin-containing vaccines in Japan .…”
Section: Introductionmentioning
confidence: 99%